Application of generalized failure mechanism knowledge to reprocessing plant for proactive risk management. (December 2017) - Yasuda, Yuuya; Takahashi, Makoto
Abstract: In this study, the generalized failure mechanism knowledge (GFMK) derived from a mechanical subsystem in the Rokkasho reprocessing plant is applied to an instrumentation subsystem in the same plant in order to examine its general applicability. This study confirms that the GFMK can be applied to the instrumentation system of a backup diesel generator and that a potential failure mechanism can be successfully derived. The efficacy of the derived knowledge regarding this failure mechanism was evaluated by referring to past failure events that have occurred in the same subsystem. This study has demonstrated exactly that some of the failure modes derived by applying GFMK had actually occurred in the real plant subsystem. The importance of this observation is that these failure modes were not included in the collection of failure events utilized to derive GFMK, which implies that the GMFK can possibly be utilized to proactively identify possible failure events in a realistic scale system.